The foraging behavior of Heterotrigona itama (Cockerell) (Hymenoptera: Apidae: Meliponini) in close system rockmelon (Cucubitales: Cucurbitaceace) cultivation - Samsudin, Siti Asma’; Jamian, Syari; Adam, Nur Azura; Mazlan, Norida; Megat Wahab, Putri Edaroyati; Shilan, Mohd Syukri Tan; Wan Mohd Adnan, Wan Nur Asiah (Penerbit Universiti Kebangsaan Malaysia, 2024)
Stingless bees (Meliponini) exhibit intricate foraging behavior that is essential for their colony's survival and reproductive success. Stingless bees exhibit a diverse range of foraging strategies that are customized to their specific ecological niche. These strategies encompass both solitary and cooperative with individuals often specializing in particular tasks within the foraging process. Through sophisticated communication mechanisms, such as waggle dances and pheromone trails, stingless bees effectively coordinate foraging efforts, maximizing resource acquisition while minimizing energy expenditure. While hand pollination by humans is the typical method employed for pollinating rock melons, it is not the preferred option due to its labor-intensive and time-consuming. Through spatial analysis and community field work, this study was conducted to assess potential Heterotrigona itama (Cockerell) as pollinators in rock melon cultivation and to investigate the foraging behavior of H. itama in rock melon cultivation inside the glasshouse. The experiment was done by determining the foraging activities, floral visitation frequency and activities rate of stingless bee in rock melon cultivation inside glasshouse. Results show that H. itama flying out from hive were 1522 individuals, while 1034 individuals of stingless bees flew into hive were recorded for foraging activities. The peak hour for foraging activities by H. itama inside the glasshouse was in the morning, from 10 a.m. to 11 a.m. On floral visitation frequency, H. itama visited rock melon male flowers more frequently than female flowers. However, for activities rate, H. itama spent longer a period foraging the female flowers than the male flowers. Thus, the findings from the present study contribute to new and impactful knowledge gained by rock melon growers and are recommended as innovations in the cultural practice of modern rock melon industry.